Thermoregulation during exercise in the heat of American football players - Leites, G. T.; Cunha, G. dos S.; Pechina, M.; Teodoro, J. L.; Ozorio, R. V. B.; Pinto, R. S.; Meyer, F. (Journal of Human Sport & Exercise, 2023)
American football players might face challenges during a prolonged exercise in the heat which can lead to impairments in performance and induce heat-related illness. The purpose of this study was to verify the body temperature and sweating responses in American football players while exercising at a moderate-high intensity effort as prescribed by metabolic heat production. Seven heat-acclimatized players participated in the study. Players exercised 4×20-min bouts at moderate-high intensity as 8.0W.kg-1 of metabolic heat production, with 10min rest between them, totalizing 110min of heat exposure (39oC and 50% relative humidity). Rectal (Tre) and skin (Tsk) temperatures, heart rate (HR), metabolic heat production were measured continuously. Dehydration was calculated from Delta body mass pre-and post-exercise. Initial Tre and HR were 37.0 ± 0.3 °C and 80 ± 9 beats.min-1, respectively. Players began the trial euhydrated according to the initial urine specific gravity (1.014 ± 0.008) and colour (2.4 ± 1.4). During experimental trial, core temperature increased overtime (p < .001) resulting in a DeltaTre of 2.2 ± 0.6 °C. Average HR during exercise was 166 ± 11 beats.min-1 and weighted Tsk was 36.7 ± 0.5 °C. Sweat volume was 2.6 ± 0.3 L, resulting a % hypohydration of -3.1 ± 0.4 % reflecting a moderate level of hypohydration. Final urine specific gravity and colour were 1.024 ± 0.009 and 5.0 ± 1.0, respectively. Experimental trials were interrupted at the end of the third and the fourth exercise bouts in two players due to the respective adverse conditions: leg muscle cramps, and excessive Tre increase (reached 39.9 °C). Thermoregulation and hydration must be a major concern, mainly related to greater exercise intensities and long-time practice, inducing high hypohydration levels and risk of hyperthermia.